2019
DOI: 10.1097/rct.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings of Klippel-Trenaunay Syndrome

Abstract: We aim to review the imaging findings of Klippel-Trenaunay syndrome. This disorder characterized clinically by a triad of capillary malformations manifesting as a port-wine stain, venous varicosities typically along the lateral aspect of the lower extremities, and bone and/or soft tissue hypertrophy. Imaging of extremities shows unilateral venous varicosities, persistent embryonic veins, anomalous of the superficial and deep venous system, low-flow venolymphatic malformations, and bony and soft tissue hypertro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…KTS is a rare congenital disorder with a typical triad of physical findings that include port-wine stain (capillary malformations in the skin), unilateral bone and soft tissue hypertrophy, and venous varicosities and venous and lymphatic malformations. 21 KTS is thought to result from a gain-of-function mutation in the protein PIK3CA, leading to activation of the mTOR protein. 6 Consequently, an accumulation of endothelial cells occurs due to reduced apoptosis and defective recruitment of vascular smooth muscle cells, resulting in enlarged, convoluted venous channels.…”
Section: Discussionmentioning
confidence: 99%
“…KTS is a rare congenital disorder with a typical triad of physical findings that include port-wine stain (capillary malformations in the skin), unilateral bone and soft tissue hypertrophy, and venous varicosities and venous and lymphatic malformations. 21 KTS is thought to result from a gain-of-function mutation in the protein PIK3CA, leading to activation of the mTOR protein. 6 Consequently, an accumulation of endothelial cells occurs due to reduced apoptosis and defective recruitment of vascular smooth muscle cells, resulting in enlarged, convoluted venous channels.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 CT, MR, and US have become commonly utilized modalities in the assessment of venous anomalies. 27 To our knowledge no study in the literature has previously identified a relationship between LCIV compression and POTS. The purpose of this multiinstitutional retrospective study is to assess the prevalence of hemodynamically significant LCIV compression in a POTS population.…”
Section: Introductionmentioning
confidence: 93%
“…25,26 CT, MR, and US have become commonly utilized modalities in the assessment of venous anomalies. 27…”
Section: Introductionmentioning
confidence: 99%
“…The signal characteristics of the lesions were discussed in Part 1 of this paper. Additional common imaging findings of KTS include bony, soft tissue, and craniofacial hypertrophy, brain aneurysms and malformations, gastrointestinal and genitourinary vascular anomalies, and splenic hemangiomas 25,27–29 …”
Section: Laser Ablationmentioning
confidence: 99%
“…These are associated with venous reflux, which is wellevaluated on color duplex US. 25 Anomalies of the deep venous system, such as hypoplasia, atresia, agenesis, or aneurysms are best evaluated with magnetic resonance venography (MRV); computerized tomographic venography may be utilized but involves ionizing radiation. US may be used to detect deep venous insufficiency and thromboembolism.…”
Section: Preprocedures Imagingmentioning
confidence: 99%